TRANSLATION PROCEDURES IN THE SECRET LIFE OF PETS MOVIE SUBTITLE - Salsabila, Haniyono; Misla Geubrina; Mayasari, Mayasari (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
ABSTRACT This research discusses the analysis of translation procedures in The Secret Life of Pets movie subtitle. This research aims to find out the types of translation procedures, to analyze how the translation procedures worked in the movie subtitle of The Secret Life of Pets movie, and to find out the dominant type of translation procedure in the movie subtitle. Qualitative research is applied in this research. The data of this research are words, phrases, and clauses that are taken from The Secret Life of Pets movie as the source of data. Vinay and Darbelnet (2000) theory is used in analyzing the types of translation procedures in this research. The results of this research are (1) there are 100 total data for the seven types of translation procedures by Vinay and Darbelnet, such as thirty for borrowing, twenty for calque, seventeen for literal translation, ten for transposition, ten for modulation, twelve for equivalence, and one for adaptation, (2) The dialogues are being translated to match the target audience's cultural and linguistic traditions while keeping It’s original meaning and tone, and (3) The dominant type of translation procedure that are found in the movie subtitle is borrowing Keywords: Translation, Translation Procedures, Movie, Subtitle